Implementasi Penggunaan Aplikasi Sistem Informasi Manajemen Kepegawaian (SIMPEG) Pada Bagian Umum Sekretariat Daerah Kabupaten Gresik - Safinatun Najah; Tukiman Tukiman (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
This article analyzes the Implementation of the Personnel Management Information System (SIMPEG) in the General Section of the Regional Secretariat of Gresik Regency. This analysis uses a qualitative approach of interviews, observations, and documentation. This research applies the theory of public policy implementation from George C. Edward III, which includes four main variables, namely Communication, Resources, Disposition, and Bureaucratic Structure. The results of this study show that the overall implementation of SIMPEG is going quite well, supported by communication through official letters from BKPSDM and internal socialization, adequate resources such as trained admins and digital infrastructure, positive disposition of employees even though they still need assistance for some users, and a structured bureaucratic structure with clear SOPs. However, there are several challenges, such as the reliance on sometimes unsmooth internet access and the disapproval of some senior employees to digital change. For this reason, further efforts are needed in the form of routine training, integration with the regional financial system, and continuous monitoring by BKPSDM so that implementation can run continuously and optimally. This aims to support more efficient and transparent employee management in Gresik Regency.